A new marketing strategy for Bagaren och Kocken A study of the Finnish market - Sochon, Emilia; Svensson, Felicia (My University, 2024)
Expanding into new international markets within the business to consumer (B2C) segment can be challenging for a foreign company. An international company must consider several aspects to ensure a successful business across all its markets. This thesis digs into the specific challenges encountered by Bagaren och Kocken, a Swedish e-commerce kitchenware company, on the Finnish market. Despite its successful operations in Sweden, Norway, and Denmark, Bagaren och Kocken faces obstacles in Finland due to a lack of brand presence and understanding of the local market dynamics, including consumer preferences and behaviors. Therefore, the aim of this master’s thesis is to map the Finnish e-commerce and kitchenware market and based on this develop a new marketing strategy on the Finnish market. The research methodology comprises three key steps. Firstly, interviews were conducted with Bagaren och Kocken personnel to gain insights into their current operations in the Finnish market. Subsequently, an external situation analysis of the Finnish market was undertaken, where both interviews with industry experts and secondary data was gathered. Finally, integrating the findings from both internal and external analyses, a new marketing strategy was formulated for Bagaren och Kocken's Finnish operations. The strategy includes how the company should develop its position, current product offerings, pricing strategies, distribution channels, promotional activities, and management of customer relationships to cater to the specific needs, behaviors, and competition of the Finnish market. Considering the company’s existing ways of working, some adjustments are necessary to meet and exceed the Finnish customers’ expectations. Firstly, the company should aim for a positioning strategy of differentiation in Finland. Secondly, the same product assortment as is offered today should be kept, only incorporating smaller changes, such as adding Miele and Jhula Mokka and increasing the product mix depth of deep-oven dishes and coffee related products. Thirdly, the company should continue to work with competitive-based pricing. Promotional pricing and special event pricing should also be used, however to a limited extent. Fourthly, it is recommended to ensure that all messages and advertisements are tailored towards the Finnish market and correctly written in Finnish. Moreover, social media marketing and email marketing should be incorporated. Opening up pop-up stores in Helsinki is also suggested. Fifthly, the company should keep offering the products online, and offer deliveries with PostNord and Posti. Fossil-free deliveries should also be added. Lastly, Finnish speaking customer service personnel should be hired and a loyalty program developed. It is also important to provide clear information on the website. By aligning strategies with Finnish consumer preferences, Bagaren och Kocken can seize opportunities for market expansion and enhanced sales.
Keywords: Finland; e-commerce; kitchenware; external situation analysis; marketing strategy